Stopping Cross-Sections in Carbon of Low-Energy Atoms With Z ≤ 12 - Ormrod, John H. (My University, 1963)
This thesis is concerned with the energy loss of light atomic projectiles in thin carbon films. Chapter I gives a brief theoretical description of the processes involved and an outline of the experimental procedure. Chapter II deals with the thin carbon films used as targets in the experiments. Chapter III describes the Monte Carlo calculation used to reduce our data to information of a general form. Chapter IV contains the experimental results and Chapter V compares the results with existing data and theory.
Title: Stopping Cross-Sections in Carbon of Low-Energy Atoms With Z ≤ 12, Author: John H. Ormrod, Location: Thode